Results of the study of source conditions indicative factors of parodontal status and local immunity of oral cavity besides flying personnel of the civil aviation - G. G. Ashurov; M. K. Shokirov; S. M. Karimov (Эндодонтия Today, 2024)
AIM. Study the source condition of parodontal structures and local immunity of oral cavity besides flying composition of the civil aviation for the reason improvements of the algorithm treatment-preventive action of dentistry nature.MATERIALS AND METHODS. Organized parodontology and immunology examination of the oral cavity beside 120 flying personnel on the base of physician-sanitary part of International airport Dushanbe. Examined contingent was divided into 5 groups: flight personnel with chronic gingivitis of the light degree of gravity; with chronic gingivitis of the average degree of gravity; with chronic parodontitis of the light degree of gravity; with chronic parodontitis of the average degree of gravity: checking group of the flying composition with sound parodont. They were researched particularities of the clinical current of the chronic gingivitis and parodontitis with using of hygienic and parodontology factors and immunology condition of oral cavity.RESULTS. Inflammatory parodontal diseases beside flying composition with chronic gingivitis and parodontitis of the average degree of gravity (II, IV groups) runs more gravely, with expressed inflammatory reaction of near teeth tissues and disorders of the hygiene of oral cavity, in contrast with flying contingent I and III groups. At study of immunological conditions of oral cavity besides flying personnel of IV group revealed reduction of lysosome activity and increasing of immunoglobulin level that is indicative of reduction humeral protection of oral cavity.CONCLUSION. Called studies have shown that PMA-index, bleeding and hygiene of oral cavity indexes with high degree of validity increased, but importance of the lysosome activity reduced on the base of increasing immunoglobulin of oral liquid beside flying composition with chronic parodontitis light and average degree of gravity.